Familial risk of chronic rhinosinusitis with and without nasal polyposis: genetics or environment. Issue 4 (12th February 2015) - Oakley, Gretchen M.; Curtin, Karen; Orb, Quinn; Schaefer, Carole; Orlandi, Richard R.; Alt, Jeremiah A.
<x xml:space="preserve">Abstract</x> Background Chronic rhinosinusitis (CRS) is a highly prevalent inflammatory condition, with significant effects on morbidity and quality of life, yet little is known about its pathogenesis. Preliminary evidence suggests there is a heritable component to the multifactorial etiology of CRS; however, our understanding of this genetic susceptibility is limited. Methods Using an extensive genealogical database linked to medical records, the risk of CRS with nasal polyps (CRSwNP) and without polyps (CRSsNP) was calculated for relatives and spouses of adult probands (1638 CRSwNP and 24, 200 CRSsNP patients diagnosed between 1996 and 2011) and were compared to random population controls matched 5:1 on sex and birth year from Cox regression models. Results First‐degree relatives (1stDRs) of CRSwNP patients demonstrated a 4.1‐fold increased risk (p < 10−3) of carrying the same diagnosis, whereas second‐degree relatives (2ndDRs) demonstrated a 3.3‐fold increased risk (p < 0.004), compared to controls. In CRSsNP patients, 1stDRs were at 2.4‐fold increased risk (p < 10−15), whereas 2ndDRs were at 1.4‐fold increased risk (p < 10−15) of the same diagnosis. Third‐degree relatives (3rdDRs) had a slight increased risk at 1.1‐fold (p < 10−7). Spouses of CRSsNP patients, who likely share environmental circumstances, exhibited a 2‐fold increased risk (p < 10−15). No increased risk was observed in spouses of CRSwNP patients. Conclusion In the largest population study to date, a significant familial risk is confirmed in CRSwNP and CRSsNP, which may have a shared genetic and environmental component. Further understanding of the genetic basis of CRS and its interplay with environment factors could clarify disease etiology and lead to more effective targeted treatments.